656Risk factors for lung cancer in never-smokers in Australia. (2nd September 2021) - Cheng, Elvin; Weber, Marianne; Steinberg, Julia; Canfell, Karen; Yu, Xue Qin
Abstract: Background: Lung cancer in never-smokers (LCINS), if considered as a distinct type, would rank as Australia's eighth most deadly cancer. We investigated several demographic, lifestyle and health-related risk factors for LCINS in Australia. Methods: Using the longitudinal 45 and Up Study cohort with 267, 153 New South Wales (NSW) residents aged ≥45 years at recruitment (2006-2009), we quantified the relationship of 20 potential risk factors with LCINS. Self-reported never-smoking participants who were cancer-free at baseline were followed for incident lung cancer (LC), and adjusted hazard ratios (HR) and 95% confidence intervals (CI) were estimated using Cox regression. The NSW Cancer, Lifestyle and Evaluation of Risk (CLEAR) Study, a case-control study including 10, 781 NSW residents aged ≥18 years, was also used to examine 16 potential risk factors for LCINS. Adjusted odds ratios (OR) and 95% CI for LC were estimated using logistic regression. Results: In the 45 and Up Study, there were 226 LC cases among 132, 354 cancer-free never-smokers with a median follow-up of 5.41 years. In the CLEAR Study, there were 58 LCINS cases and 1316 cancer-free never-smoking controls. After adjusting for potential confounders, analyses of both datasets showed that Asian-born participants had a higher risk of LCINS than those born elsewhere: cohort HR = 2.83 (95% CI: 1.64-4.89) and case-control OR = 3.78 (95% CI: 1.19-12.05). Conclusions: Our findings support the growing evidence that never-smokers born in Asia are at higher risk of developing LC than those born elsewhere. Key messages: Region of birth could be considered when assessing potential LC risk among never-smokers.